The Effects of Provincial Competitiveness Index (PCI) Components on Private Enterprise Satisfaction with Local Business Environment: The Case of Phu Tho Province - Chi Dung, Ho; Long, Nguyen Hoai; Oanh, Dinh Van; Thanh, Pham Thi Kim; Dung, Tran Viet (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2018)
The Provincial Competitiveness Index (PCI) is used to assess the local attractiveness to investors in Vietnam. However, studies on how the assessment of investors including private enterprises on the components of PCI relates to their satisfaction with local business environment are still sparse. Therefore, this study was conducted to investigate the effect of private enterprise satisfaction with PCI components on their satisfaction with the local business environment. Through the survey carried out in Phu Tho, the results showed: (1) the level of private firm satisfaction with PCI components; (2) the effect of satisfaction with each PCI component variable on the overall satisfaction with that factor; (3) the effect of satisfaction with PCI components on private firm satisfaction with local business environment. Following the quantitative research, qualitative research by in-depth interviews with individual investors was conducted to find out the causes and suggestion for some solutions to improve the level of business satisfaction and PCI of a province.